Corporate governance and firm performance: case of selected oil companies in Nigeria (2020)
Separating ownership from managerial control in publicly traded firms made corporate governance a matter of necessity, due to the possibility of principal agent problem. Mostly, managers protect their own self-interest without regard for shareholders’ returns on investment, this often lead to agency conflict and consequent loss. Previous studies have focused mainly on manufacturing and banking sector, however, paucity of information exists in areas of oil firms over the years. Hence, effect of corporate governance on performance of listed oil companies in Nigeria from 2009 to 2018 were investigated. Secondary data sourced from Nigeria stock exchange covering 2009 to 2018 were used to examine effect of corporate governance on performance of six oil companies in Nigeria. Data collected include; board size, executive directors’ number, non-executive directors’ number, audit committees’ number, net annual income, shareholders’ equity, net profit/margin, assets for the period, while board composition, return on assets and equity were generated. Data collected were analysed using Cross Sessional Random Effects Model (REM) of regression analysis. Unit root test indicated that all variables were stationary at level. Audit committee (0.803277), (4.363851) exhibited a positive relationship with firms’ performance, though insignificant, while board composition (-2.647377)(-2.647377) and board size (-0.546097) (-2.948961) had an inverse relationship, though significant with ROE and ROA. All the variables jointly influence firms’ performance positively with R2(0.587999,0.597182) and adjusted R2 (0.544499,0.584174) value, respectively. Audit committees enhances firms’ performance; all variables jointly improve firms’ performance. Measures should be put in place to increase audit committees independence and the extent to which they disclose corporate governance information